Clinical case of duodenal ulcer with perforation in a woman after a planned cesarean section. - M. K. Chekan; T. A. Loskutova; Ye. V. Fomicheva (Medičnì Perspektivi)
Gastric or duodenal ulcer with perforation - a heavy, death threatening, complication of peptic ulcer disease, especially in pregnant or postpartum. The occurrence of this complication in the postpartum period is a common cause of late diagnosis, delayed surgical treatment and poor outcome for the patient. There are several problems that contribute to the late diagnosis of perforated ulcer: rare incidence, difficulty in identifying common signs, stiff muscles of the anterior abdominal wall and localization of pain in the stomach due to abdominal extension by a pregnant uterus, pain due to caesarean section, absence of ulcer history, the young age of patients, an unusual course of the disease. Complaints and clinical presentation are often regarded by physicians as complications of carried out obstetric surgery, which leads to late diagnosis. The paper describes a clinical case of duodenal ulcer with perforation, which occurred on the second day after a planned caesarean section, as a rare but life threatening complications. The patient underwent laparotomy with suturing of the perforation and drainage of the abdominal cavity. It should be noted that, despite the fact that complications of peptic ulcer disease is a rare phenomenon among women in labor, it should be in anamnesis taking to pay special attention to information that may indicate the presence of disorders of the diseases of gastrointestinal tract. In case of unfavorable postoperative course after abdominal labor an acute surgical pathology should not be excluded.